A fluorescent probe for glycosaminoglycans applied to the detection of dermatan sulfate by a mix-and-read assay - Rappold, Melissa; Warttinger, Ulrich; Krämer, Roland (Molecules, 2017)
Glycosaminoglycans are complex biomolecules of great biological and medical importance. The quantification of glycosaminoglycans, in particular in complex matrices, is challenging due to their inherent structural heterogeneity. Heparin Red, a polycationic, fluorescent perylene diimide derivative, has recently emerged as a commercial probe for the convenient detection of heparins by a mix-and-read fluorescence assay. The probe also detects glycosaminoglycans with a lower negative charge density than heparin, although with lower sensitivity. We describe here the synthesis and characterization of a structurally related molecular probe with a higher positive charge of +10 (vs. +8 of Heparin Red). The superior performance of this probe is exemplified by the quantification of low dermatan sulfate concentrations in an aqueous matrix (quantification limit 1 ng/mL) and the detection of dermatan sulfate in blood plasma in a clinically relevant concentration range. The potential applications of this probe include monitoring the blood levels of dermatan sulfate after administration as an antithrombotic drug in the absence of heparin and other glycosaminoglycans.